ChemInform Abstract: Exploiting Photoredox Catalysis for the Synthesis of Tetra‐ and Di‐Hydrofurans. Issue 35 (September 2015) - Fumagalli, Gabriele; Boyd, Scott; Greaney, Michael F.
Abstract A mild and high yielding methodology for concomitant C—C and C—O bond formation across activated alkenes is described.